Experimental Pain in Healthy Human Subjects: Gender Differences in Nociception and in Response to Ibuprofen - Walker, Judith S.; Carmody, John J. (Anesthesia and analgesia, 1998)
We used electrically induced pain in healthy young subjects to study gender differences in nociception and the analgesic efficacy of ibuprofen. Cutaneous stimulation of the earlobe allowed measurement of pain detection thresholds and maximal pain tolerance. Drug and placebo were each administered twice using a double-blind, randomized, multiple cross-over design. Male subjects had greater stimulus thresholds (lower nociception) compared with female subjects (18 +/- 0.3 vs 15 +/- 0.3 volts, mean +/- SEM; n = 10 in each group) and a greater pain tolerance (24 +/- 0.4 vs 21 +/- 0.4 volts). Response variability was also greater in the male subjects, yet only the men exhibited a statistically significant analgesic response to ibuprofen (deltavolts; ibuprofen versus placebo: 2.80 +/- 0.33 vs -0.18 +/- 0.34; P < 0.05, n = 10). None of these results could be attributed to pharmacokinetic differences. The finding that ibuprofen was less effective in women than in men has potential clinical significance, especially as a factor in the response variability to nonsteroidal antiinflammatory drugs. In this study, we examined ibuprofen, a widely used nonsteroidal antiinflammatory drug, for its ability to reduce experimental pain. We found that it had such properties in healthy young male subjects but not in young female subjects. This is a paradox because many of the painful conditions for which nonsteroidal antiinflammatory drugs are used (e.g., rheumatoid arthritis) occur more often in women.